Comparing the ability of arousal control in male and female athletes using mental imagery and biofeedback methods - Bahram Ghafari; Mehdi Shahbazi (University of Tehran, 2015)
The aim of this research was to investigate the ability of arousal control in male and female athletes using mental imagery and biofeedback methods. Participants were 30 male and female athlete students of Tehran University (mean aged 23) who were assigned into two homogeneous groups based on Vividness of Movement Imagery Questionnaire 2. Participants were given acoustic biofeedback during three stages of pretest, posttest, and follow-up test while their scores in arousal indexes such as heart rate, body temperature, and galvanic skin response were recorded. In posttest, they were asked to mentally imagine their performance under competition circumstance and in follow-up test they had to attempt to lower their arousal level using deep breathing and acoustic biofeedback technique. Results of analysis of variance with repeated measures and independent t test indicated that there is a significant difference between groups mean scores in follow-up test in three indexes of heart rate, body temperature, and galvanic skin response (p≤0/05). This finding suggests that male students have higher ability in arousal control compared with female students.